Composite mechanisms for improving Bubble Rap in delay tolerant networks. Issue 1 (13th January 2014) - Jain, Sweta; Kishore, Nikhitha; Chawla, Meenu; Soares, Vasco N.G.J.
Abstract : Delay tolerant networks (DTNs) are a subset of mobile ad hoc networks where connections are sparse and intermittent. This often results in a network graph which is rarely connected which introduces a challenge in message forwarding because of a lack of end‐to‐end connectivity towards the destination. Recently, social‐based forwarding algorithms are gaining popularity because of the social nature displayed by the node movements in a DTN, especially in application areas like the pocket switched networks. The social‐based metrics like community, similarity, centrality etc. are used to determine the carrier to which a node has to forward its message. Composite methods are used to improve the performance of Bubble Rap social‐based forwarding algorithm. In the proposed mechanism, a new social metric termed 'friendship' has been introduced along with a time‐to‐live (TTL)‐based 'threshold' and acknowledgement (ACK) IDs. Real trace data and working day movement models are used for simulations in the opportunistic network environment simulator to demonstrate that the proposed algorithm gives better delivery ratio than the original Bubble Rap algorithm.